Randomized clinical trial of high versus low inferior mesenteric artery ligation during anterior resection for rectal cancer. Issue 4 (8th June 2018) - Fujii, S; Ishibe, A; Ota, M; Watanabe, K; Watanabe, J; Kunisaki, C; Endo, I
Abstract: Background: The optimal level for inferior mesenteric artery ligation during anterior resection for rectal cancer is controversial. The aim of this randomized trial was to clarify whether the inferior mesenteric artery should be tied at the origin (high tie) or distal to the left colic artery (low tie). Methods: Patients were allocated randomly to undergo either high- or low-tie ligation and were stratified by surgical approach (open or laparoscopic). The primary outcome was the incidence of anastomotic leakage. Secondary outcomes were duration of surgery, blood loss and 5-year overall survival. Results: Some 331 patients entered the trial between June 2006 and September 2012. The trial was stopped prematurely as recruitment was slow. Seven patients were excluded after randomization but before operation because of procedural changes. High tie and low tie were performed in 164 and 160 patients respectively. The incidence of anastomotic leakage was not significantly different (17·7 versus 16·3 per cent respectively; P = 0·731). The incidence of severe complications requiring intervention was 2·4 versus 5·0 per cent for high and low tie respectively ( P = 0·222). In multivariable analysis, risk factors for anastomotic leakage included male sex (odds ratio 4·36, 95 per cent c.i. 1·56 to 12·18) and distance of the tumour from the anal verge (odds ratio 0·99, 0·98 to 1·00). At 5 years there were no significant differences in overall (87·2 versus 89·4 per cent respectively; P = 0·386) and disease-free (76·3 versus 77·6 per cent; P = 0·765) survival. Conclusion: The level of ligation of the inferior mesenteric artery does not significantly influence the rate of anastomotic leakage. Registration number: NCT01861678 (https://clinicaltrials.gov ). Graphical Abstract: The aim of this study was to clarify whether the inferior mesenteric artery should be tied at the origin (high tie, HT) or distal to the left colic artery (low tie, LT) by randomized trial. The incidence of anastomotic leakage (HT : LT, %) showed no significant differences for all grades (17·7 : 16·3), grade 2 or higher (9·8 : 8·8), and grade 3 or higher (2·4 : 5·0). LT was not an effective procedure for the prevention of anastomotic leakage in an anterior resection. Comparable outcomes after 'high-tie' and 'low-tie'